Agro-tourism as a rural development strategy in Korea - 이성우 (서울대학교, 2007)
This paper investigates diverse policy experiences of enhancing agro-tourism in Korea. Since the campaign of “rural theme village” as a rural development strategy is closely related with the discussion of agro-tourism, this paper looks into past and recent streams of agro-tourism strategies pursued by the central government in Korea. This paper examines why agro-tourism has emerged as one of major rural development strategies in Korea. Along with a historical background of agro-tourism development in Korea, this paper presents the current and possible future characteristics of green tourism for rural community development in Korea. This paper also examines the perceived role of tourism in rural development. Special attention is paid to the ways in which the development of tourist attractions encourages changes in attitudes towards both rural resources assessment and entrepreneurship. Presenting success and failure stories, this paper also considers why the development of tourist attractions has been slow in rural areas of Korea, reviewing restraints, reservations, and problems identified during the last decade.
Keywords: Policy evaluation; Rural tourism; Rural theme village; Korea; Policy evaluation; Rural tourism; Rural theme village; Korea